Aktualisasi Nilai-nilai Pendidikan Agama Islam Dalam Kehidupan Santri di Madrasah Ibtidakiyah NW Al-Akhyar Bagik Polak Barat Kecamatan Labuapi Kabupaten Lombok Barat Provinsi Nusa Tenggara Barat Tahun Pelajaran 2019-2020 - Mastur (Jurnal LENTERA: Jurnal Studi Pendidikan, 2020)
Education is a shared responsibility between family, community and school (government). The 1998 GBHN states that education is life-long and is carried out in the family, school and community environment, therefore education is a shared responsibility between family, community and government. In the case of religious education, in general it is a shared responsibility, especially for families, communities and schools or madrasahs. In collecting data in this journal, using the following methods: Observation Methods, Library Methods and Documentary Methods. In this regard, we can draw conclusions 1. Religious education plays an important role in our lives and lives and is an effort that must be carried out for students because religious ideals have a higher and wider value than others. Religion concerns matters of belief or faith which require accuracy and persistence and we must really understand how to present it to students so that the desired goals can be achieved properly. 2. The duties and responsibilities of parents as educators have a very big influence on students. Because the parents in the family / household are the first to be recognized by the child. 3. Children are beings who are developing towards perfection (adult). Step by step the child's development is the development of the mental functions of the child as a whole. Each connected with the other at each level of development requires guidance and leadership. So this is where the role and function of parents in providing guidance and education to children. 4. The aim of religious education is to prepare children so that one day it is enough to do jobs that make themselves happy according to the norms and rules of the Islamic religion. Creating children so that they can be devoted to their parents, know and practice the teachings of their religion, both those related to their personality, society and those directly related to their god. 5. The condition of the teacher and the development of his students is quite advanced and is developing in accordance with the era of development, especially in the fields of education and culture